A comment on Jumping The Gun: How Dictators Got Ahead Of Their Subjects (2023) - Sharmi Sen; Adit Maitra; Alistair Cameron (Institute for Replication (I4R), 2023)
Instructions: Hariri & Wingender add new nuance to the traditional wisdom that economic modernisation is a path to democracy. They show that the diffusion of repressive, military technologies, causes a decline in the number of democratisations in the following years, and argue that this is because of a greater ability to forcefully oppress popular dissent. We conduct a robustness replication exercise, focussed on three tests: i) Are findings robust to alternative weightings of individual technologies in the instrument for country-aggregate military technology? ii) Is high leverage in individual countries, regions or time periods driving the global findings? iii) Are the strength of the IV and its independence of important macroeconomic indicators a chance occurrence? The main findings of the paper are largely robust to these tests.
Keywords: 330